Is the femoral neck-shaft angle an independent risk factor for hip fractures? An observational study - Obande, Bernard O.; Iyidobi, Emmanuel C.; Eyichukwu, Gabriel O.; Nwadinigwe, Cajetan U.; Ekwunife, Remigus T.; Ede, Osita (International Journal of Research in Orthopaedics, 2019)
Background: The femoral neck-shaft angle (FNSA) has been implicated in the aetiology of hip fractures. The longer moment arm of a higher FNSA has been theorized to impart a greater deforming force to the greater trochanter, which may cause a hip fracture. Methods: A prospective study that involves adults with hip fractures and a control group matched for age and sex. The FNSA of both groups were measured on an anteroposterior X-ray of the pelvis. The mean FNSA were compared with a paired samples t-test, and a binary logistic regression analysis was run with the FNSA as a predictor variable and the presence of hip fracture as an outcome variable. Results: A total of 150 patients were recruited for the study, 75 per group. The mean age of patients with hip fractures was 71.30 years (S.D.=14.34), and that of the control group was 73.94 years (S.D.=12.55), p=0.264. The mean FNSA of the study group was 133.96o (S.D.=3.77) while that of the control group was 131.05o (S.D.=3.86), p<0.001. Increasing FNSA imparts a higher risk of having a hip fracture, O.R.=1.24 (95% C.I, 1.12-1.37). Conclusions: Individuals with higher FNSA demonstrated a significantly increased risk of developing hip fractures. However, the exact cut-off point of the FNSA, which predisposes to the risk of these fractures, remains to be elucidated.